The Teaching of Essays, Articles and Letter Writing: Cooperative Teaching Approach - Ayodele, Victoria; Akinkurolere, Susan; Ariyo, Kayode; Mahmud, Olayemi; Abuya, Eromosele (Asian Research Journal of Arts & Social Sciences, 2017)
English Language occupies a central place in Nigeria as the official language. Today, teachers are calling for more effective methods of communicating information and assisting the students in the learning process because the issue of poor performances in English Language examinations is alarming and cannot be glossed over. It is noted that new pedagogies are being introduced to the curriculum from time to time; and approaches from other fields such as anthropology, psychology, sociology are encouraged. This indicates that innovations and constant improvements are needed in the teaching process. One of the innovative ways of improving students’ learning and performance is by encouraging cooperative approach. The ‘cooperative writing approach’ to teaching of English Language involves role-playing and role-shifting. The best bet in teaching is the creative and practical component. Thus, cooperative model is a recently developed socio-cultural method of the teaching aspects of a topic in any subject or course in a participatory and roleshifting manner. This approach is sociological and anthropological in orientation because it allows students to relate well in learning process. Hence, the paper identifies ways by which select topics could be taught in schools by giving practical examples. The discoveries in the teaching of students through the cooperative model will significantly improve teaching and learning of English as a Second Language in Nigeria.
Keywords: English language; Students; Teaching; Cooperation; Classroom